EFFECT OF SUN, VITAMIN D AND SKIN CANCER - Yulia Farida Yahya; Theresia L. Toruan; Yuli Kurniawati; Fifa Argentina; Susanti Budiamal; Aryati Fadhila; Nyimas Nursyarifah; Dedi Deddy; Ahmad Ligar Suherman (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Indonesia, especially in South Sumatra, is a tropical country where people are exposed to sunlight all the time. The sunlight exposure is both chronic and intermittent, which can cause both beneficial and detrimental effects. One of the examples of the detrimental effects are the increased incidence of skin cancer. Meanwhile, the beneficial effect is the formation of vitamin D in the body that stimulates bone formation, increases body resistance, and prevents skin cancer. At this time, there is an increase in the incidence of skin cancer, and many Indonesian people are deficient in Vitamin D. Currently, the people need to get an explanation through health workers at the TkI Health Facilities and Rivai Abdulah Hospital. It is necessary to increase knowledge about sunlight, the benefits of Vitamin D for health, and its effects on the incidence of skin cancer in health workers.